NEW YORK ASSEMBLY DEFEATS BILL TO PROHIBIT SMOKING IN PUBLIC PLACES. - DIONNE EJ JR (Tufts Archival Research Center, 2007)
Copy; Article from the New York Times on the defeat of a ban on smoking in public places in the New York State Assembly. Demonstrates conservative sentiment that the bill was anti-labor and too restrictive. Shows the liberal argument that cigarette interests got people "riled up." Discusses the technicalities of legislation, including whether or not to include restaurants.